Assessment of magnetism and magnetocrystalline anisotropy of (Mn $$_x$$ Fe $$_{1-x}$$ ) $$_2$$ P $$_{1-y}$$ Si $$_y$$ (x,y = 0 or 1/3) compounds for permanent magnets - Priti Rani; Ali H. Reshak; Renu Singla; Jyoti Thakur; Sarvesh Kumar; Timothy A. Hackett; Dania Ali; Manish K. Kashyap (Scientific Reports)
Abstract In order to calculate the prospects for new transition-metal rich and rare-earth free permanent magnets, we have investigated the electronic and magnetic properties of Fe $$_{2}$$ P and related Mn- or/and Si-substituted compounds using full potential linearized augmented plane wave (FPLAPW) method under generalized gradient approximation (GGA) exchange-correlation (XC) functional. In agreement with the experiment, our calculated total magnetic moment and magnetocrystalline anisotropy (MCA) for Fe $$_{2}$$ P are found to be 3.03 $$μ$$ $$_B$$ /f.u. and 538 $$μ$$ eV/f.u. (2.58 MJ/m $$^{3}$$ ), respectively. We find that the substitution of Mn or/and Si in Fe $$_{2}$$ P not only enhances the magnetization but also boosts the maximum energy product by preserving the hard magnetic behavior. Our theoretical predictions provide useful insights to enhance magnetization with tolerable loss of MCA for Mn or/and Si substituted Fe $$_{2}$$ P. Thus, we propose rare-earth free prospective candidates for permanent magnets through Fe $$_{2}$$ P based compounds.